What students learn matters : towards a 21st century curriculum. (OECD, 2020)
For the first time, the OECD Future of Education and Skills 2030 project conducted comprehensive curriculum analyses through the co-creation of new knowledge with a wide range of stakeholders including policy makers, academic experts, school leaders, teachers, NGOs, other social partners and, most importantly, students. This report is one of six in a series presenting the first-ever comparative data on curriculum at the content level summarising existing literature, examining trends in curriculum change with challenges and strategies, and suggesting lessons learned from unintended consequences countries experienced with their curriculum reforms. This report highlights that economic, societal and environmental changes are happening rapidly and technologies are developing at an unprecedented pace, but education systems are relatively slow to adapt. Time lag in curriculum redesign refers to the discrepancies between the content of today's curriculum and the diverse needs of preparing students for the future. The OECD Learning Compass can serve as a guide for adjusting to the new demands of education systems with regards to curriculum, pedagogies, assessments, governance structure, educational management, and the role of students. Innovative approaches to curriculum design that may minimise time lags include: digital curriculum; personalised curriculum; cross-curricular content and competency-based curriculum; and flexible curriculum.